Effect of different staking methods and stem pruning on yield and quality of summer tomato (Bangladesh Journal of Agricultural Research, 2016)
The study was carried out during summer of 2012 with BARI hybrid tomato 4, planted in the Olericulture farm of Bangladesh Agriculture Research Institute, Joydebpur, Gazipur, Bangladesh to find out the response of plants to some staking and pruning treatments on yield, fruit quality and cost of production. A two factor experiment consisting of three staking methods and four level of pruning, laid out in complete block design with three repetitions. Plants were staked on inverted V? shaped staking, high platform and string. The plants were pruned to two stem, three stem, four stem and no pruning as control. Results showed that significantly the highest total number of fruits per plant (37.1), marketable fruits per plant (33.7), yield per plant (1.68 kg) and total yield (44.6 t/ha) were produced by the plants having the treatment string staking with four stem. The highest fruit set (43.50%) was found in the plants staking with string having three stems. Plants grown on string staking allowing two stem gave the maximum length (4.71 cm), diameter (4.83 cm) and weight (53.4g) of single fruit as well as maximum fruit firmness (3.43 kg-f cm-2). From the economic point of view, it was apparent that summer tomato produced by string staking with four stem pruning exhibited better performance compared to other treatment combinations in relation to net return and BCR (2.10).Bangladesh J. Agril. Res. 41(3): 419-432, September 2016